EF24, a schistosomicidal curcumin analog: Insights from its synthesis and phenotypic, biochemical and cytotoxic activities. (1st December 2022) - Badoco, Fernanda R.; Paula, Lucas A.L.; Orenha, Renato P.; Mendes, Tiago M.F.; Squarisi, Iara S.; El-Sakkary, Nelly; Loiola, Messias C.; Katz, Naftale; Tavares, Denise C.; Sairre, Mirela I.; Parreira, Renato Luis T.; Janku Cabral, Fernanda; et al.
Abstract: Praziquantel (PZQ) is the only drug available for community-based control programs which aim to reduce the prevalence and morbidity associated with schistosomiasis. Here, we synthesized and evaluated the schistosomicidal, biochemical and cytotoxic activities of EF24, a synthetic curcumin analog, against different isolates of Schistosoma mansoni. EF24 elicited marked phenotypic alterations at 10 μM against schistosomula and 42-day-old adult worms of the Naval Medical Research Institute (NMRI) isolate . EF24 had 50% effective concentration (EC50 ) values of <10 μM against the Luis Evangelista (LE), Sergipe (SE), Belo Horizonte (BH) and Belo Horizonte less sensitive to PZQ (BH < PZQ) isolates of adult S. mansoni ; however, the respective sensitivities of these isolates differed. Changes in the parasite included, vacuolization of the tegument and focal lysis of the interstitial tissue and muscle layers. Against 28-day-old juvenile worms (LE isolate), EF24 was about three times more potent than PZQ. After 6 h at 12.5 μM, EF24 increased reactive oxygen species (ROS) and the activity of the antioxidant enzyme, glutathione-S-transferase (GST), by 32 and 19% in female and male adult worms, respectively. By contrast, after 6 h at 12.5 μM glutathione reductase (GR) activity decreased by 43 and 30%, and glutathione peroxidase (GPx) activity decreased by 67 and 44% in females and males, respectively. EF24 was less cytotoxic to mammalian host cells than to S. mansoni, with selectivity indexes (SIs) of 1.8–3.4 and 2.7–7.5 for juvenile and adult worms, respectively. Given the current evidence for the in vitro schistosomicidal effect of EF24, the structure-activity relationship of additional analogs to identify new candidates for schistosomiasis treatment is warranted . Graphical abstract: Image 1 Highlights: EF24 induces phenotypic changes in S. mansoni (NMRI isolate) schistosomula and adults. EF24 exhibits EC50 values < 10 μM against four Brazilian S. mansoni isolates evaluated. EF24 induces ultrastructural changes in adult S. mansoni . EF24 induces changes in various oxidative stress parameters in adult S. mansoni . EF24 is less cytotoxic to mammalian cells than S. mansoni .